2022
DOI: 10.3390/nu14030529
|View full text |Cite
|
Sign up to set email alerts
|

Role of Creatine Supplementation in Conditions Involving Mitochondrial Dysfunction: A Narrative Review

Abstract: Creatine monohydrate (CrM) is one of the most widely used nutritional supplements among active individuals and athletes to improve high-intensity exercise performance and training adaptations. However, research suggests that CrM supplementation may also serve as a therapeutic tool in the management of some chronic and traumatic diseases. Creatine supplementation has been reported to improve high-energy phosphate availability as well as have antioxidative, neuroprotective, anti-lactatic, and calcium-homoeostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 270 publications
(299 reference statements)
0
12
0
9
Order By: Relevance
“…Potential effects of CrM consumption as a therapeutic nutritional agent in clinical conditions have been suggested for some chronic and traumatic diseases (acute injuries, spinal cord injury, postoperative orthopedic recovery, muscular dystrophy, immobility, and atrophy due to muscle disuse, among others) [ 90 ]. Furthermore, CrM supplementation could help in maintaining or improving clinical outcomes by improving physiological adaptations during rehabilitation processes in patients with substantially reduced skeletal muscle contractile capacity [ 91 ], as in the case of sports injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Potential effects of CrM consumption as a therapeutic nutritional agent in clinical conditions have been suggested for some chronic and traumatic diseases (acute injuries, spinal cord injury, postoperative orthopedic recovery, muscular dystrophy, immobility, and atrophy due to muscle disuse, among others) [ 90 ]. Furthermore, CrM supplementation could help in maintaining or improving clinical outcomes by improving physiological adaptations during rehabilitation processes in patients with substantially reduced skeletal muscle contractile capacity [ 91 ], as in the case of sports injuries.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be converted into phosphocreatine by creatine kinase, an important metabolite involved in ATP metabolism, supplying energy to muscles, nerve tissue, and other organs requiring significant energy . Furthermore, creatine supplementation can modulate acidosis, inflammation, and oxidative stress in cells . Increasingly, researchers have suggested that metabolites can manipulate cellular signaling by directly binding or covalently post-translationally modifying certain proteins to affect cell growth. , Although the direct target of creatine remains to be elucidated, creatine has been proven to modulate Smad2/3 signaling through activation of the monopolar spindle 1 .…”
Section: Discussionmentioning
confidence: 99%
“…These experimental data suggest that stabilizing enzymes such as CKm, which play a central role in regulating the metabolic feedback of mitochondrial respiration, attenuate TBI-induced toxicity. This idea is based on the ability of this guanidine compound to stabilize the contact sites of the inner and outer mitochondrial membranes and prevent the opening of mitochondrial permeability pores and, consequently, the excess of oxygen free radicals [55][56][57].…”
Section: Discussionmentioning
confidence: 99%